MODEL MEDIASI DALAM HUBUNGAN ANTARA INTELLECTUAL CAPITAL DISCLOSURE, NILAI PERUSAHAAN, DAN FINANCIAL PERFORMANCE - Desak Nyoman Sri Werastuti (Jurnal Keuangan dan Perbankan, 2014)
This study aimed to determine the disclosure effect of intellectual capital on firm value through the financial performance of companies listed on the Indonesia Stock Exchange in the period of 2008 to 2012. Intellectual capital measurement used a model developed by Pulic (1998, 1999, 2000), which assessed the efficiency of value added as a result of the company's intellectual capabilities (value added intellectual coefficient-VAICTM). Financial performance in this study was measured using return on assets (ROA) and firm value was measured by using the Market to Book Value (MtBV). The samples in this study were taken using purposive. The final samples in this study were 1.135 observations. This hypothesis was tested using path analysis. The results showed that (1) the disclosure of intellectual capital had a positive effect on financial performance; (2) disclosure of intellectual capital had no effect on firm value; (3) financial performance was able to mediate the relationship between intellectual capital disclosure and corporate value.